MULTIMEDIA INTERACTIVE TOOLS IN PROGRAMMING TEACHING (Journal of Information Technologies in Education (ITE), 2011)
Use of multimedia interactive tools while teaching programming for freshmen, is considered. The use of multiple-mouse applications are proposed for raising student's activities.
Keywords: approach for programming teaching; interactive board; interactive lesson; mouse mischief; multiple-mouse application